Caracterização macro, meso e microscópica das estruturas frágeis do corpo arenítico conglomerático da região de Santana do Acaraú (CE) e seu embasamento circundante - Carvalho, Júlio Alexandre Almeida de (2005)
The structural framework of the sedimentary basins usually plays an important role in oil prospects and reservoirs. Geometry, interconectivity and density of the brittle features developed during basin evolution could change the permo-porous character of the rocks involved in generation, migration and entrapment of fluid flow. Once the structural characterization of the reservois using only sub-surface data is not an easy task, many studies are focused in analogous outcrops trying to understand the main processes by which brittle tectonic is archieved. In the Santana do Acaraú region (Ceará state, NE Brazil) a pack of conglomeratic sandstone (here named CAC) has its geometry controlled mainly by NE trending faults, interpreted as related to reactivation of a precambrian Sobral Pedro II Lineament (LSP-II). Geological mapping of the CAC showed a major NE-SW trending synform developed before its complete lithification during a dextral transpression. This region was then selected to be studied in details in order of constrain the cretaceous deformation and so help the understanding the deformation of the basins along the brazilian equatorial margin. In order to characterize the brittle deformation in different scales, I study some attributes of the fractures and faults such as orientation, density, kinematic, opening, etc., through scanlines in satellite images, outcrops and thin sections. The study of the satellite images showed three main directions of the macrostructures, N-S, NE-SW and E-W. Two of theses features (N-S and E-W) are in aggreement with previous geophysical data. A bimodal pattern of the lineaments in the CAC´s basement rocks has been evidenciated by the NE and NW sets of structures obtained in the meso and microscale data. Besides the main dextral transpression two others later events, developed when the sediments were complety lithified, were recognized in the area. The interplay among theses events is responsible for the compartimentation of the CAC in several blocks along within some structural elements display diferents orientations. Based on the variation in the S0 orientation, the CAC can be subdivided in several domains. Dispite of the variations in orientations of the fractures/faults in the diferents domains, theses features, in the meso and microscopic scale, are concentrated in two sets (based on their trend) in all domains which show similar orientation of the S0 surface. Thus the S0 orientation was used to group the domains in three major sets: i) The first one is that where S0 is E-W oriented: the fractures are oriented mainly NE with the development of a secondary NW trending; ii) S0 trending NE: the fractures are concentrated mainly along the trend NW with a secondary concentration along the NE trend; iii) The third set, where S0 is NS the main fractures are NE and the secondary concentration is NW. Another analized parameter was the fault/fracture length. This attribute was studied in diferent scales trying to detect the upscale relationship. A terrain digital model (TDM) was built with the brittlel elements supperposed. This model enhanced a 3D visualization of the area as well as the spatial distribution of the fault/fractures. Finally, I believe that a better undertanding of the brittle tectonic affecting both CAC and its nearby basement will help the future interpretations of the tectonic envolved in the development of the sedimentary basins of the brazilian equatorial margin and their oil reservoirs and prospects, as for instance the Xaréu field in the Ceará basin, which subsurface data could be correlated with the surface ones